Exploring the impacts of mindfulness and yoga upon childbirth outcomes and maternal health: an integrative review. Issue 3 (3rd December 2019) - Van der Riet, Pamela; Francis, Lyn; Rees, Angela
Abstract : Background: Foetal development and the long‐term outcomes of the infant are influenced by the intrauterine environment. Strategies to enhance maternal health in pregnancy are needed to improve health outcomes for childbearing women and babies, advancing the well‐being of our general population. Aim: To synthesise the existing literature to determine the impacts of mindfulness and yoga practice upon birth outcomes and maternal health. Methods: An integrative literature review using Whittemore and Knafl's framework was undertaken in 2016–2017. Two search strategies included database peer‐reviewed journal articles and ancestry searching, that is exploring the reference list of relevant research articles. After screening and checking the eligibility, a total of 12 articles were included in this review. Data analysis involved coding, visual displays, thematic analysis and comparison, and conclusion drawing. Results: The results of this review identified a broad theme that mindfulness and yoga practice is associated with improved maternal mental health antenatally and postnatally. Subthemes have been presented under the central theme including the following: increased mindfulness correlates with decreased fear of childbirth; reduced symptoms of anxiety and depression; and supportive group settings found to be beneficial by pregnant women. Conclusion: The evidence presented in this review suggests that mindfulness and yoga practice are feasible and cost‐effective interventions to enhance maternal mental health, particularly for women experiencing mental health challenges. Mindfulness and yoga practised regularly in the antenatal period can significantly promote the health of pregnant women and potentially their developing babies.